Effect of integrated nutrient management on mungbean (Vigna radiata) under custard apple (Annona squamosa) based agri-horti system in Vindhyan region, Uttar Pradesh - DEBBARMA, MALATI; MEENA, RAM SWAROOP; SINGH, S P; SINGH, AJEET; KUMAR, SUNIL; GURJAR, D S; PANKAJ, BHANUPRIYA (The Indian Journal of Agricultural Sciences, 2020)
Agroforestry is recognized as most diversified sustainable system to support farmers income. In order to assess the effect of nutrient management system under agro forestry based cropping system, a field study was conducted during kharif season of 2017 on mungbean [Vigna radiata (L.) Wilczek] at the Agricultural Research Farm, Rajiv Gandhi South Campus, Banaras Hindu University, Barkachha, Mirzapur (UP). The experimental trial was conducted in simple RBD with four replications and six treatments, viz. 75% RDF+ Rhizobium, 75% RDF+ Biochar+ Rhizobium, 100% RDF+ Rhizobium, 75% RDF+ FYM+ Rhizobium, 75% RDF+ Vermicompost+ Rhizobium and 75% RDF + pressmud+ Rhizobium. Results revealed that highest growth parameters such as plant height, dry matter accumulation, leaf area index, trifoliate leaves, chlorophyll content, root nodules/plant and dry weight of root nodules and yield attributes and was observed with the application of 75% RDF + pressmud+ Rhizobium than other nutrient sources. Furthermore, highest gross return, net return was observed with the application of 75% RDF + vermicompost + Rhizobium. However, highest B:C ratio was observed with the application of 100% RDF + Rhizobium.